ACADEMIC FLOW DITINJAU DARI SELF REGULATED LEARNING PADA SISWA SMP X DI SEMARANG - Amin Mustofa; I Rheny Arum Permitasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2024)
This research tests the hypothesis whether there is a relationship between the level of self-regulated learning and the level of academic flow in SMP X students in Semarang. Data collection involved 210 students. The hypothesis testing process uses the Product Moment correlation method from Karl Pearson with calculation results showing a correlation coefficient value of 0.686 with a correlation significance level of 0.00 or showing a significance level of p < 0.01. These results indicate that there is empirical evidence that there is a very significant positive relationship between self-regulated learning and academic flow in students. Thus, it can be concluded that the hypothesis proposed in this research is accepted. This conclusion can also be defined as the higher the level of self-regulated learning that students have, the higher the level of academic flow. Likewise, vice versa, the lower the level of self-regulated learning, the lower the student's academic flow. Keywords: self-regulated learning, academic flow